2023
DOI: 10.1002/eji.202250355
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic reticular cells provide a supportive niche for lymph node–resident macrophages

Abstract: The lymph node (LN) is home to resident macrophage populations that are essential for immune function and homeostasis, but key factors controlling this niche are undefined. Here, we show that fibroblastic reticular cells (FRCs) are an essential component of the LN macrophage niche. Genetic ablation of FRCs caused rapid loss of macrophages and monocytes from LNs across two in vivo models. Macrophages co‐localized with FRCs in human LNs, and murine single‐cell RNA‐sequencing revealed that FRC subsets broadly exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…Previous work has demonstrated that FRCs in the lymph node paracortex of mice similarly express CCL2, which regulates monocyte trafficking to the paracortex (31). Furthermore, human cultured FRCs derived from lymph nodes or tonsils have also been shown to constitutively express CCL2, IL-6, CXCL8, and/or CXCL1 (15,16,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that FRCs in the lymph node paracortex of mice similarly express CCL2, which regulates monocyte trafficking to the paracortex (31). Furthermore, human cultured FRCs derived from lymph nodes or tonsils have also been shown to constitutively express CCL2, IL-6, CXCL8, and/or CXCL1 (15,16,28).…”
Section: Discussionmentioning
confidence: 99%
“…While there are extensive studies evaluating the function of FRCs in vivo in murine models and in vitro on TCPS, there is a need for 3D models of the human paracortex that can evaluate the trafficking of human DCs and T-cells into the lymph node. Although many molecular pathways have been shown to be conserved between human and mouse FRCs, human FRCs have been shown to differentially express a variety of cytokines and inflammatory pathways compared to mouse FRCs (13,28). Thus, in comparison to in vivo mouse models, in vitro models of the lymph node paracortex utilizing human FRCs may serve as better predictive models for preclinically testing immunotherapies targeting lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…They are characterized by the expression of smooth muscle actin and desmin. The fibroblastic reticular cell tumor is thought to be a neoplasm originating from putative stromal fibroblastic reticular cells [3,[20][21][22].…”
Section: Fibroblastic Reticular Cellsmentioning
confidence: 99%
“…Whether and to what extent MRC-derived DLL1 or other notch ligands affect myeloid cell homeostasis in the splenic marginal zone is, however, still unresolved. In contrast, the contribution of the macrophage master regulator colony-stimulating factor 1 (CSF1, macrophage colony-stimulating factor) for balancing of myeloid cell populations has recently been clarified ( Bellomo et al, 2020 ; D’Rozario et al, 2023 ; Fig. 2 a ).…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%
“…2 a ). CSF1 is produced by human and mouse LN FRCs and has been shown to stimulate macrophage development and activation in vitro ( D’Rozario et al, 2023 ). In the murine spleen, CSF1 generated by Ccl19-Cre + MRCs appears to be essential for the maintenance of CD169 + metallophilic macrophages ( Bellomo et al, 2020 ).…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%